Addressing the Challenge of Withdrawal of Lump Sum Retirement Benefit Payments in South Africa : Lessons from Australia - Marumoagae, Motseotsile Clement (Comparative and International Law Journal of Southern Africa, 2020)
This paper discusses the South African government’s approach in addressing its concern regarding members of retirement funds who are unable to care for themselves when they reach retirement. The paper highlights the challenge of such members’ increased risk of not being able to keep the same standards of living as during their working life and outliving the retirement benefits which they received when they retired. This paper evaluates the impact of receiving lump sum payments either before reaching the retirement age or upon retirement on the ability of members to care for themselves during retirement. It further examines whether the government’s intervention through the intended compulsory preservation of retirement benefits would lessen the risks of members outliving their retirement benefits. The paper argues that while the thought of introducing compulsory preservation seems sound, compulsion would not necessarily cater adequately for the varied needs of all retirement fund members. Further this paper argues, that South Africa should draw lessons from Australia and allow those members who are able to justify the need to be paid their entire benefit when they exit their funds, to receive their benefits in full.